Industry Perspective on Translational and Clinical Pharmacology Aspects of Viral-based Gene Therapies and Vaccines—Key Considerations and Learnings From Approved Products - Hardik Mody; Jatin Narula; Prathap Nagaraja Shastri; Dale Miles; Yun Liu; Vittal Shivva; Jimit Raghav; Gillie Roth; Anshul Gupta; Bahru Habtemariam; Salvatore Iovino; Steven Louie; et al. (The AAPS Journal, 2026)

Decadal migration timing and temporal variation in dive behavior of an endangered beluga whale population - Kasey P. Ryan; Sean F. Ryan; Mads Peter Heide-Jørgensen; Steven H. Ferguson; Sasha R. X. Dall; James D. Roth; Cortney A. Watt (Frontiers in Marine Science, 2026)
Introduction Understanding migration timing and movement behavior is critical for predicting population responses to environmental changes. The beluga whale ( Delphinapterus leucas ) population in Cumberland Sound, Nunavut, is currently endangered due to historical and ongoing overharvesting. Methods By comparing satellite telemetry data from two distinct time periods (1998–1999 and 2006–2008), we evaluated beluga whale dive behavior and migration timing in relation to environmental and seasonal factors. To infer potential prey shifts, we compared the proportion of dives deeper than 100 m, where Arctic cod ( Boreogadus saida ) are typically found, with shallower dives indicative of capelin ( Mallotus villosus ) foraging. Dive behavior was analyzed in relation to seasonal progression (day of year), time period, ice cover, bottom depth, and sex using mixed-effects models. Migration timing was evaluated using latitudinal thresholds and a transect line to identify the timing and variability of southward autumn movements relative to sea ice formation. Results We found significant seasonal (day of year) variation in dive behavior, with deep dives increasing from September to December. Additionally, there was a notable shift to more shallow dives in the second time period compared to the first, suggesting a change in foraging from Arctic cod to capelin. We found that the whales’ initial movements out of their summering area appeared largely independent of ice phenology, while their movements later in their migration were highly variable. Discussion The shift in prey likely occurred due to changes in prey distribution driven by warmer ocean temperatures, which may have negative long-term impacts on population health. Some of these behavioral trends contrasted with those of other beluga whale populations, emphasizing the need for population-specific management strategies to support long-term survival of the Cumberland Sound beluga whale population.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Assessing predictions on fitness effects of missense variants in HMBS in CAGI6 - Jing Zhang; Lisa Kinch; Panagiotis Katsonis; Olivier Lichtarge; Milind Jagota; Yun S. Song; Yuanfei Sun; Yang Shen; Nurdan Kuru; Onur Dereli; Ogun Adebali; Muttaqi Ahmad Alladin; et al. (Human Genetics, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Identifying predictors of translocation success in rare plant species - Joe Bellis; Oyomoare Osazuwa‐Peters; Joyce Maschinski; Matthew J. Keir; Elliott W. Parsons; Thomas N. Kaye; Michael Kunz; Jennifer Possley; Eric Menges; Stacy A. Smith; Daniela Roth; Debbie Brewer; et al. (Conservation Biology, 2024)
The fundamental goal of a rare plant translocation is to create self‐sustaining populations with the evolutionary resilience to persist in the long term. Yet, most plant translocation syntheses focus on a few factors influencing short‐term benchmarks of success (e.g., survival and reproduction). Short‐term benchmarks can be misleading when trying to infer future growth and viability because the factors that promote establishment may differ from those required for long‐term persistence. We assembled a large ( n = 275) and broadly representative data set of well‐documented and monitored (7.9 years on average) at‐risk plant translocations to identify the most important site attributes, management techniques, and species’ traits for six life‐cycle benchmarks and population metrics of translocation success. We used the random forest algorithm to quantify the relative importance of 29 predictor variables for each metric of success. Drivers of translocation outcomes varied across time frames and success metrics. Management techniques had the greatest relative influence on the attainment of life‐cycle benchmarks and short‐term population trends, whereas site attributes and species’ traits were more important for population persistence and long‐term trends. Specifically, large founder sizes increased the potential for reproduction and recruitment into the next generation, whereas declining habitat quality and the outplanting of species with low seed production led to increased extinction risks and a reduction in potential reproductive output in the long‐term, respectively. We also detected novel interactions between some of the most important drivers, such as an increased probability of next‐generation recruitment in species with greater seed production rates, but only when coupled with large founder sizes. Because most significant barriers to plant translocation success can be overcome by improving techniques or resolving site‐level issues through early intervention and management, we suggest that by combining long‐term monitoring with adaptive management, translocation programs can enhance the prospects of achieving long‐term success.

Trophic Structure and a Temporal Shift in Trophic Diversity of Mobile Consumers in a Subarctic Estuary - Jillian R. St. George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuaries and Coasts, 2024)
Quantifying trophic relationships within and between species in terms of trophic position, ontogeny and trophic diversity provides information on community-level structure and function. Little attention has been focused on examining the trophic structure and temporal changes of communities in freshwater-marine coupled systems in the subarctic and associated impacts of anthropogenic activity on trophic interactions. Therefore, the objective of this study was to quantify the trophic position of mobile consumers (15 species in total) within the lower Churchill River area (Churchill, Manitoba, Canada), examine trophic position variation in relation to ontogeny, and measure the trophic diversity of a fish assemblage before (1993–1995) and after (2019–2020) the installation of the Churchill River weir in the late 1990s. We used stable isotopes (δ 13 C and δ 15 N) to quantify individual and group-level variation in trophic position of thirteen fish species and two seal species and also assessed six community-level metrics of a three fish species assemblage between time periods. Overall, species that mainly foraged on freshwater resources occupied lower trophic positions than species that mainly consumed marine resources. Trophic position increased with fish age only in cisco, fourhorn sculpin, Greenland cod and northern pike. A temporal shift from a trophically diverse to a more trophically redundant fish assemblage occurred between 1993–1995 and 2019–2020. As a result, these predator species now play similar trophic roles. Information on the long-term change in trophic structure of this sub-Arctic estuarine system may help with understanding how anthropogenic activity and climate change have influenced the trophic diversity of a fish assemblage inhabiting this system.

Habitat coupling dynamics of mobile consumers along a freshwater and marine resource gradient in a sub-Arctic estuarine system - Jillian R. St George; Stephen D. Petersen; James D. Roth; Steven H. Ferguson; David J. Yurkowski (Estuarine, Coastal and Shelf Science, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Enhanced detection and estimation of regional S-phases using the 3-component ARCES array - Steven J. Gibbons; Johannes Schweitzer; Tormod Kværna; Michael Roth (Journal of Seismology, 2019)

Airflow Simulations in Infant, Child, and Adult Pulmonary Conducting Airways - Jessica M. Oakes; Steven C. Roth; Shawn C. Shadden (Annals of Biomedical Engineering, 2018)

A model-based assay design to reproduce in vivo patterns of acute drug-induced toxicity - Lars Kuepfer; Olivia Clayton; Christoph Thiel; Henrik Cordes; Ramona Nudischer; Lars M. Blank; Vanessa Baier; Stephane Heymans; Florian Caiment; Adrian Roth; David A. Fluri; Jens M. Kelm; et al. (Archives of Toxicology, 2018)

Increased blubber cortisol in ice-entrapped beluga whales (Delphinapterus leucas) - Marci R. Trana; James D. Roth; Gregg T. Tomy; W. Gary Anderson; Steven H. Ferguson (Polar Biology, 2016)

Assessing vulnerability: an integrated approach for mapping adaptive capacity, sensitivity, and exposure - Shawn W. Margles Weis; Vera N. Agostini; Lynnette M. Roth; Ben Gilmer; Steven R. Schill; John English Knowles; Ruth Blyther (Climatic Change, 2016)

Protein Kinase B (Akt) and Mitogen-Activated Protein Kinase p38α in Retinal Ischemic Post-Conditioning - John C. Dreixler; Ajay Sampat; Afzhal R. Shaikh; Michael Alexander; Marcus M. Marcet; Steven Roth (Journal of Molecular Neuroscience, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

RNase 1 genes from the family Sciuridae define a novel rodent ribonuclease cluster - Steven J. Siegel; Caroline M. Percopo; Kimberly D. Dyer; Wei Zhao; V. Louise Roth; John M. Mercer; Helene F. Rosenberg (Mammalian Genome, 2009)

Keeping the blood flowing—plasminogen activator genes and feeding behavior in vampire bats - Åsa Tellgren-Roth; Katharina Dittmar; Steven E. Massey; Cecilia Kemi; Christian Tellgren-Roth; Peter Savolainen; Leslie A. Lyons; David A. Liberles (The Science of Nature, 2009)

Quantifying the effects of voluntary contraction and inter-stimulus interval on the human soleus H-reflex - Richard B. Stein; Kristen L. Estabrooks; Steven McGie; Michael J. Roth; Kelvin E. Jones (Experimental Brain Research, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The predatory behavior of wintering Accipiter hawks: temporal patterns in activity of predators and prey - Timothy C. Roth; Steven L. Lima (Oecologia, 2007)

Determinants of predation risk in small wintering birds: the hawk’s perspective - Timothy C. Roth; Steven L. Lima; William E. Vetter (Behavioral Ecology and Sociobiology, 2006)

Polymorphic variation of CYP1A1 is associated with the risk of gastric cardia cancer: a prospective case?cohort study of cytochrome P-450 1A1 and GST enzymes - Mark J. Roth; Christian C. Abnet; Laura Lee Johnson; Steven D. Mark; Zhi Wei Dong; Philip R. Taylor; Sanford M. Dawsey; You-Lin Qiao (Cancer Causes & Control, 2004)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)